PC / ABS alloy material as well as preparation method and application thereof

By using flat chopped high-boron glass fiber in PC/ABS alloy materials, the problems of the material in mechanical properties and warping deformation are solved, and better mechanical properties and wave transmissibility are achieved, and it is suitable for millimeter-wave radar exterior decoration parts.

CN119875343APending Publication Date: 2025-04-25GUANGDONG JUSHI CHEM CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411900349.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-23
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

The existing PC/ABS alloy materials are difficult to meet the requirements of automobiles, home appliances, electronics and other fields in terms of mechanical properties, and are prone to warping and deformation.

Method used

A flat, chopped high-boron glass fiber reinforced PC/ABS alloy material is used to improve the mechanical properties and wave transmissibility of the material and reduce warpage by controlling the proportion of each component.

Benefits of technology

The better mechanical properties, low warpage and wave transmissibility of PC/ABS alloy materials have been achieved, making it have broad application prospects in millimeter-wave radar exterior decoration parts.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention discloses a PC / ABS (polycarbonate / acrylonitrile butadiene styrene) alloy material as well as a preparation method and application thereof. The PC / ABS alloy material comprises the following components in parts by weight: 30-80 parts of polycarbonate resin, 10-40 parts of ABS resin, 10-30 parts of flat chopped high-boron-content glass fibers, 2-5 parts of a compatilizer, 0.1-1.0 part of an antioxidant and 0.1-1.0 part of a lubricant. Due to the unique shape of the flat chopped glass fiber, the flat chopped glass fiber tends to flow in the injection molding process instead of rolling and tumbling like rod-shaped glass fiber, so that the flow dispersity is better, the anisotropy is reduced, the warping and deformation of the material are reduced, the material is favorably processed into a thin product, and the product quality is improved. By selecting the high-boron-content glass fiber, the wave permeability of the PC / ABS alloy can be further improved, so that the PC / ABS alloy has a wide application prospect in millimeter-wave radar outer decorating parts.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of polymer materials, and in particular to a PC / ABS alloy material and a preparation method and application thereof. Background Art

[0002] In high-speed and high-frequency transmission technology, the use of low dielectric constant materials can increase the signal transmission speed of smart terminals, reduce signal delays, and reduce signal losses. With the advent of the 5G era, the millimeter wave frequency band is high, the signal penetration is poor, and the attenuation is large, making 5G communications more dependent on low dielectric constant materials. PC resin has a small dielectric constant, good wave transmission performance, relatively low cost, and meets the requirements of weather resistance and lightweight. PC material has become the mainstream choice for millimeter wave radar exterior decoration parts, but its fluidity is poor and processing is difficult. ABS resin has good comprehensive performance and is easy to process and mold. Therefore, PC / ABS alloy combines the excellent properties of ABS and PC, that is, the moldability of ABS material and the wave transmission, mechanical properties, temperature resistance, and UV resistance of PC. It is a polymer alloy with comprehensive performance.

[0003] However, PC / ABS alloys are difficult to fully meet the requirements of the automotive, home appliances, electronic appliances and other fields in terms of mechanical properties. Therefore, glass fiber reinforced PC / ABS alloy materials are often used on the market to significantly improve their mechanical properties. However, since conventional glass fibers are rod-shaped structures with obvious orientation in the material, the shrinkage of the material in the flow and perpendicular flow directions is greatly different, which makes the material prone to warping and deformation. Summary of the invention

[0004] The present invention aims to solve at least one of the above-mentioned technical problems existing in the prior art. To this end, the purpose of the present invention is to provide a PC / ABS alloy material and a preparation method and application thereof, wherein the PC / ABS alloy material has good mechanical properties and also maintains good fluidity, wave permeability and low warpage.

[0005] In order to achieve the above object, the technical solution adopted by the present invention is:

[0006] The first aspect of the present invention provides a PC / ABS alloy material, comprising the following components in parts by weight: 30 to 80 parts of polycarbonate resin, 10 to 40 parts of ABS resin, 10 to 30 parts of flat short-cut high-boron glass fibers, 2 to 5 parts of a compatibilizer, 0.1 to 1.0 parts of an antioxidant, and 0.1 to 1.0 parts of a lubricant.

[0007] In the present invention, due to its unique shape, the flat chopped glass fibers tend to flow during the injection molding process rather than rolling and tumbling like rod-shaped glass fibers. Therefore, the flow dispersion is better and the anisotropy is reduced, thereby reducing the warping and deformation of the material, which is conducive to processing into thin products. The use of high-boron glass fibers can further improve the wave transmittance of PC / ABS alloys, making it have broad application prospects in millimeter-wave radar exterior decorative parts.

[0008] In some embodiments of the present invention, the PC / ABS alloy material comprises the following components in parts by weight: 50 to 70 parts of polycarbonate resin, 10 to 30 parts of ABS resin, 15 to 30 parts of flat short-cut high-boron glass fibers, 3 to 5 parts of a compatibilizer, 0.3 to 0.8 parts of an antioxidant, and 0.3 to 0.8 parts of a lubricant.

[0009] In some embodiments of the present invention, the PC / ABS alloy material comprises the following components in parts by weight: 50 to 65 parts of polycarbonate resin, 10 to 25 parts of ABS resin, 15 to 25 parts of flat short-cut high-boron glass fibers, 3 to 5 parts of a compatibilizer, 0.3 to 0.8 parts of an antioxidant, and 0.3 to 0.8 parts of a lubricant.

[0010] In some embodiments of the present invention, the viscosity average molecular weight of the polycarbonate resin is 20,000 to 30,000, such as 20,000 to 28,000, 20,000 to 25,000, or 22,000 to 24,000; the melt index of the polycarbonate resin at 300° C. and 1.2 kg is 15 to 25 g / 10 min, such as 15 to 23 g / 10 min, or 12 to 14 g / 10 min.

[0011] In some embodiments of the present invention, the ABS resin contains acrylonitrile monomer, butadiene monomer and styrene monomer; the content of the acrylonitrile monomer is 25wt% to 30wt%, such as 26wt% to 30wt%, 26wt% to 28wt%; the content of the butadiene monomer is 20wt% to 26wt%, such as 21wt% to 23wt%; the content of the styrene monomer is 46wt% to 54wt%, such as 50wt% to 52wt%; the melt index of the ABS resin at 220°C and 10kg is 38 to 44g / 10min.

[0012] In some embodiments of the present invention, the boron content of the flat chopped high-boron glass fiber is 18wt% to 24wt%, such as 19wt%, 20wt%, 21wt%, 22wt%, 23wt%, etc.; the fiber length is 25 to 30mm, such as 26mm, 27mm, 28mm, 29mm, etc.; the fiber cross-sectional width is 7 to 10μm, such as 7.5μm, 8μm, 8.5μm, 9μm, 9.5μm, etc.; the fiber cross-sectional flatness ratio is 1:3 to 1:6, such as 1:4, 1:5, etc.; the dielectric constant of the fiber is 3 to 4, such as 3.6±0.2.

[0013] In some embodiments of the present invention, the compatibilizer includes maleic anhydride grafted polypropylene, maleic anhydride grafted polyethylene, and maleic anhydride grafted polyolefin elastomer; wherein the grafting rate of the maleic anhydride grafted polypropylene is 1.2% to 2.0%, such as 1.5% to 1.8%.

[0014] In some embodiments of the present invention, the antioxidant includes at least one of a hindered phenol antioxidant, a hydroxylamine antioxidant, and a phosphite antioxidant; such as antioxidant 1010, antioxidant 168 or a mixture thereof, such as a mixture of antioxidant 1010 and antioxidant 168 in a mass ratio of 1:1 to 3.

[0015] In some embodiments of the present invention, the lubricant includes at least one of polyethylene wax, magnesium stearate, calcium stearate, and ethylene bisstearamide; such as a mixture of polyethylene wax and calcium stearate; such as a mixture of polyethylene wax and calcium stearate in a mass ratio of 1 to 3:1.

[0016] The second aspect of the present invention provides a method for preparing the PC / ABS alloy material, comprising the following steps: mixing, melting, extruding and granulating the components to obtain the PC / ABS alloy material.

[0017] In some embodiments of the present invention, the preparation method of the PC / ABS alloy material comprises the following steps: uniformly mixing the polycarbonate resin, ABS resin, compatibilizer, antioxidant, and lubricant, adding the mixture to the main feed port of a twin-screw extruder, adding the flat chopped high-boron glass fiber to the side feed port of the twin-screw extruder, melting, extruding, and granulating to obtain the PC / ABS alloy material.

[0018] In some embodiments of the present invention, the stirring rate of the mixing is 200-400 rpm, such as 250 rpm; and the time is 5-15 min, such as 10 min.

[0019] In some embodiments of the present invention, the feeding speed of the side feeding port corresponds to that of the main feeding port.

[0020] In some embodiments of the present invention, during the melting, the temperature of zone 1 of the twin-screw extruder is controlled to be 260-270°C, the temperature of zone 2 is 270-280°C, the temperature of zone 3 is 280-290°C, the temperature of zone 4 is 290-300°C, the temperature of zone 5 is 290-300°C, the temperature of zone 6 is 280-290°C, and the head temperature is 280-290°C, the material is pulled out, pelletized, and the PC / ABS alloy material is obtained.

[0021] In some embodiments of the present invention, the aspect ratio of the twin-screw extruder is 52:1, the main engine speed is 300-450 rpm, and the vacuum degree is ≥0.08 Mpa.

[0022] In some embodiments of the present invention, the rotation speed during the granulation is controlled to be 10 to 25 rpm.

[0023] The third aspect of the present invention provides a millimeter wave radar device, the shell of which is made of the PC / ABS alloy material.

[0024] The beneficial effects of the present invention are:

[0025] 1) PC resin has a small dielectric constant, excellent wave transmission performance, relatively low cost, and meets the requirements of weather resistance and lightweight, making it the mainstream choice for millimeter wave radar exterior decoration parts. However, it has poor fluidity and is difficult to process. The present invention improves the processability of PC resin by adding ABS resin.

[0026] 2) The present invention selects flat short-cut high-boron glass fiber reinforced PC / ABS alloy material and controls the proportion of each component so that the components can play a synergistic role. While improving the mechanical properties and warpage, it can also maintain the good wave transmittance of the PC / ABS alloy material, so that it has broad application prospects in the field of signal transmission. DETAILED DESCRIPTION

[0027] The present invention is further described in detail below by specific examples. Unless otherwise specified, the raw materials, reagents or devices used in the examples and comparative examples can be obtained from conventional commercial sources or can be obtained by prior art methods. Unless otherwise specified, the experiments or test methods are conventional methods in the art.

[0028] In the following examples or comparative examples, the material information is as follows:

[0029] Polycarbonate resin 1: FN2200, Idemitsu Co., Ltd., Japan, viscosity average molecular weight 22000-24000, melt index 12g / 10min;

[0030] Polycarbonate resin 2: FN2800, Idemitsu Co., Ltd., Japan, viscosity average molecular weight 26000-28000; melt index 10g / 10min;

[0031] ABS resin 1: PA-765, Chimei, Taiwan, China, acrylonitrile monomer content is 26wt%, butadiene monomer content is 22wt%, styrene monomer content is 52wt%, and melt index is 42g / 10min;

[0032] ABS resin 2: PA-757, Chimei, Taiwan, China, acrylonitrile monomer content is 30wt%, butadiene monomer content is 26wt%, styrene monomer content is 44wt%, and melt index is 28g / 10min;

[0033] Flat chopped high-boron glass fiber 1: TLD-CS-T442A, Taishan Fiberglass, boron content is 21wt%, fiber flatness ratio is 1:4, fiber length is 25-30mm, dielectric constant is 3.6;

[0034] Flat short-cut high-boron glass fiber 2: TLD-CS-T445A, Taishan Fiberglass, boron content is 21wt%, fiber flatness ratio is 1:6, fiber length is 25-30mm, dielectric constant is 3.6;

[0035] Flat chopped glass fiber: TLD-CS-T432B, Taishan Fiberglass, boron content is 6wt%, fiber flatness ratio is 1:4, fiber length is 25-30mm, dielectric constant is 5.4;

[0036] Rod-shaped short-cut high-boron glass fiber: TLD-CS-T453S, Taishan Fiberglass, boron content is 21wt%, fiber cross-sectional diameter is 10μm, fiber length is 25-30mm, dielectric constant is 3.6;

[0037] Rod-shaped chopped glass fiber: TLD-CS-T436S, Taishan Fiberglass, boron content is 6wt%, fiber cross-sectional diameter is 10μm, fiber length is 25-30mm, dielectric constant is 5.4;

[0038] Compatibilizer: Maleic anhydride grafted polypropylene (KT-1), grafting rate 1.6%, Yitian New Materials;

[0039] Antioxidants: Antioxidant 1010, Antioxidant 168, BASF;

[0040] Lubricant: Polyethylene wax (BN500), Bonny Chemical; Calcium stearate (CV500), Hanwei.

[0041] Example 1

[0042] This embodiment prepares a high-transmittance and low-warpage PC / ABS alloy material, and the specific process is as follows:

[0043] The high-transmittance and low-warpage PC / ABS alloy material is composed of the following raw materials in parts by weight:

[0044] 60 parts of polycarbonate resin 1; 15 parts of ABS resin 1; 20 parts of flat short-cut high-boron glass fiber 1; 4 parts of compatibilizer; 0.5 parts of antioxidant; 0.5 parts of lubricant.

[0045] The preparation method of high-transmittance and low-warpage PC / ABS alloy material is:

[0046] 1) Pour polycarbonate resin, ABS resin, compatibilizer, antioxidant and lubricant into a mixer, set the mixing speed of the mixer to 250 rpm, the mixing time to 10 min, and pour into the main feeding port of a twin-screw extruder after uniform blending, and add the flat short-cut high-boron glass fiber into the side feeding port of the twin-screw extruder;

[0047] 2) Control the temperature of the twin-screw extruder zone 1 to 260°C, zone 2 to 270°C, zone 3 to 280°C, zone 4 to 290°C, zone 5 to 300°C, zone 6 to 300°C, and die head to 290°C, pull out the material, cut into pellets, and remove particles and powder that do not meet the specifications after passing through a vibrating screen, mix them evenly in the finished product bin, and obtain high-transmittance and low-warpage PC\ABS alloy material standard particles.

[0048] The length-to-diameter ratio of the twin-screw extruder is 52:1, the main engine speed is 350rpm, the vacuum degree is ≥0.08Mpa, the pelletizer speed is 15rpm, and the vibrating screen is a linear double-axis vibrating screen with an aperture of 6mm.

[0049] Example 2

[0050] This embodiment prepares a high-transmittance and low-warpage PC / ABS alloy material, and the specific process is as follows:

[0051] The high-transmittance and low-warpage PC / ABS alloy material is composed of the following raw materials in parts by weight:

[0052] 65 parts of polycarbonate resin 1; 15 parts of ABS resin 1; 15 parts of flat short-cut high-boron glass fiber 1; 4 parts of compatibilizer; 0.5 parts of antioxidant; 0.5 parts of lubricant.

[0053] The preparation method of the high-transmittance and low-warpage PC / ABS alloy material in this embodiment is carried out with reference to Example 1.

[0054] Example 3

[0055] This embodiment prepares a high-transmittance and low-warpage PC / ABS alloy material, and the specific process is as follows:

[0056] The high-transmittance and low-warpage PC / ABS alloy material is composed of the following raw materials in parts by weight:

[0057] 55 parts of polycarbonate resin 1; 15 parts of ABS resin 1; 25 parts of flat short-cut high-boron glass fiber 1; 4 parts of compatibilizer; 0.5 parts of antioxidant; 0.5 parts of lubricant.

[0058] The preparation method of the high-transmittance and low-warpage PC / ABS alloy material in this embodiment is carried out with reference to Example 1.

[0059] Example 4

[0060] This embodiment prepares a high-transmittance and low-warpage PC / ABS alloy material, and the specific process is as follows:

[0061] The high-transmittance and low-warpage PC / ABS alloy material is composed of the following raw materials in parts by weight:

[0062] 55 parts of polycarbonate resin 1; 20 parts of ABS resin 1; 20 parts of flat short-cut high-boron glass fiber 1; 4 parts of compatibilizer; 0.5 parts of antioxidant; 0.5 parts of lubricant.

[0063] The preparation method of the high-transmittance and low-warpage PC / ABS alloy material in this embodiment is carried out with reference to Example 1.

[0064] Example 5

[0065] This embodiment prepares a high-transmittance and low-warpage PC / ABS alloy material, and the specific process is as follows:

[0066] The high-transmittance and low-warpage PC / ABS alloy material is composed of the following raw materials in parts by weight:

[0067] 60 parts of polycarbonate resin 1; 15 parts of ABS resin 1; 20 parts of flat short-cut high-boron glass fiber 2; 4 parts of compatibilizer; 0.5 parts of antioxidant; 0.5 parts of lubricant.

[0068] The preparation method of the high-transmittance and low-warpage PC / ABS alloy material in this embodiment is carried out with reference to Example 1.

[0069] Example 6

[0070] This embodiment prepares a PC / ABS alloy material, which is different from the embodiment 1 in that the polycarbonate resin 1 is replaced with the polycarbonate resin 2. The specific process is as follows:

[0071] The PC / ABS alloy material is composed of the following raw materials in parts by mass:

[0072] 60 parts of polycarbonate resin 2; 15 parts of ABS resin 1; 20 parts of flat short-cut high-boron glass fiber 1; 4 parts of compatibilizer; 0.5 parts of antioxidant; 0.5 parts of lubricant.

[0073] The preparation method of the PC / ABS alloy material in this embodiment is carried out with reference to Example 1.

[0074] Example 7

[0075] This embodiment prepares a PC / ABS alloy material, which is different from the embodiment 1 in that the ABS resin 1 is replaced with the ABS resin 2. The specific process is as follows:

[0076] The PC / ABS alloy material is composed of the following raw materials in parts by mass:

[0077] 60 parts of polycarbonate resin 1; 15 parts of ABS resin 2; 20 parts of flat short-cut high-boron glass fiber 1; 4 parts of compatibilizer; 0.5 parts of antioxidant; 0.5 parts of lubricant.

[0078] The preparation method of the PC / ABS alloy material in this embodiment is carried out with reference to Example 1.

[0079] Comparative Example 1

[0080] This comparative example prepares a PC / ABS alloy material, which differs from Example 1 in that no ABS resin is added. The specific process is as follows:

[0081] The PC / ABS alloy material is composed of the following raw materials in parts by mass:

[0082] 75 parts of polycarbonate resin 1; 20 parts of flat short-cut high-boron glass fiber 1; 4 parts of compatibilizer; 0.5 parts of antioxidant; 0.5 parts of lubricant.

[0083] The preparation method of the PC / ABS alloy material in this comparative example is carried out with reference to Example 1.

[0084] Comparative Example 2

[0085] This comparative example prepares a PC / ABS alloy material, which differs from Example 1 in that the flat short-cut high-boron glass fiber 1 is not added. The specific process is as follows:

[0086] The PC / ABS alloy material is composed of the following raw materials in parts by mass:

[0087] 80 parts of polycarbonate resin 1; 15 parts of ABS resin 1; 4 parts of compatibilizer; 0.5 parts of antioxidant; 0.5 parts of lubricant.

[0088] The preparation method of the PC / ABS alloy material in this comparative example is carried out with reference to Example 1.

[0089] Comparative Example 3

[0090] This comparative example prepares a PC / ABS alloy material, which is different from Example 1 in that the flat short-cut high-boron glass fiber 1 is replaced with a flat short-cut glass fiber. The specific process is as follows:

[0091] The PC / ABS alloy material is composed of the following raw materials in parts by mass:

[0092] 60 parts of polycarbonate resin 1; 15 parts of ABS resin 1; 20 parts of flat chopped glass fibers; 4 parts of compatibilizer; 0.5 parts of antioxidant; and 0.5 parts of lubricant.

[0093] The preparation method of the PC / ABS alloy material in this comparative example is carried out with reference to Example 1.

[0094] Comparative Example 4

[0095] This comparative example prepares a PC / ABS alloy material, which is different from Example 1 in that the flat short-cut high-boron glass fiber 1 is replaced with rod-shaped short-cut glass fiber. The specific process is as follows:

[0096] The PC / ABS alloy material is composed of the following raw materials in parts by mass:

[0097] 60 parts of polycarbonate resin 1; 15 parts of ABS resin 1; 20 parts of rod-shaped short glass fibers; 4 parts of compatibilizer; 0.5 parts of antioxidant; and 0.5 parts of lubricant.

[0098] The preparation method of the PC / ABS alloy material in this comparative example is carried out with reference to Example 1.

[0099] Comparative Example 5

[0100] This comparative example prepares a PC / ABS alloy material. The difference from Example 1 is that the flat short-cut high-boron glass fiber 1 is replaced with a rod-shaped short-cut high-boron glass fiber. The specific process is as follows:

[0101] The PC / ABS alloy material is composed of the following raw materials in parts by mass:

[0102] 60 parts of polycarbonate resin 1; 15 parts of ABS resin 1; 20 parts of rod-shaped short-cut high-boron glass fiber; 4 parts of compatibilizer; 0.5 parts of antioxidant; 0.5 parts of lubricant.

[0103] The preparation method of the PC / ABS alloy material in this comparative example is carried out with reference to Example 1.

[0104] Test example

[0105] This test example tests the performance of the PC / ABS alloy material obtained in the embodiment or comparative example, and the specific process is as follows:

[0106] Melt index: tested according to ISO 1133 standard;

[0107] Tensile strength: tested according to ISO 527 standard;

[0108] Bending strength: tested according to ISO 178 standard;

[0109] Flexural modulus: tested in accordance with ISO 178 standard;

[0110] Izod notched impact strength: tested in accordance with ISO 180 standard;

[0111] Warpage test: Inject PC\ABS alloy material into a 210mm×140mm×2mm sample. After the sample is warped, fix one side of the sample and measure the vertical distance between the highest point of the warping on the other side and the tabletop. The smaller the distance, the flatter the material.

[0112] Wave transmittance: The test was carried out in accordance with GJB 7954-2012 radar wave transmittance test method for radar wave transmittance of materials, and the wave transmittance of PC\ABS alloy materials was tested at 2.4GHZ and 18GHZ electromagnetic wave frequencies respectively.

[0113] The performance test results of the PC\ABS alloy materials of Examples 1 to 7 are shown in Table 1, and the performance test results of the PC\ABS alloy materials of Comparative Examples 1 to 5 are shown in Table 2.

[0114] Table 1

[0115]

[0116]

[0117] Table 2

[0118] Test items unit Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Comparative Example 5 Melt index g / 10min 7 22 18 13 13 Tensile Strength MPa 100 78 97 92 93 Bending Strength MPa 109 84 102 97 98 Flexural modulus MPa 3664 2357 3537 3379 3391 Notched impact strength <![CDATA[KJ / m 2 ]]> 12 9 15 11 11 Warpage mm 1.4 0.5 1.2 2.1 2.1 Wave transmittance (2.4GHZ) % 91 93 78 77 86 Wave transmittance (18GHZ) % 90 91 76 75 84

[0119] From the above test data, we can know that:

[0120] 1) It can be seen from the test results of Examples 1 to 7 and Comparative Examples 1 to 5 that compared with ordinary rod-shaped chopped glass fibers, the addition of flat chopped glass fibers can effectively improve the fluidity of PC / ABS alloy materials and reduce the warpage of PC / ABS alloy materials. This is because, due to its unique shape, flat glass fibers tend to flow like flaky mica during the injection molding process, rather than rolling and tumbling like traditional rod-shaped glass fibers, so the flow dispersion is better and the anisotropy is reduced, thereby reducing the warpage and deformation of the parts, and when the fiber flatness ratio is 1:4, the warpage of the PC / ABS alloy material is the smallest. Flat glass fibers with a high boron content have a small dielectric constant, which can improve the mechanical properties and warpage while maintaining the good wave transmittance of PC / ABS alloys, making them have broad application prospects in millimeter-wave radar exterior decorative parts.

[0121] 2) From the test results of the embodiment and comparative example 1, it can be seen that the PC composite material without adding ABS resin has a low melt index, poor fluidity, and is not easy to process and shape.

[0122] 3) From the test results of the embodiment and comparative example 2, it can be seen that the mechanical properties of the PC\ABS alloy material without adding flat chopped glass fibers are relatively low.

[0123] 4) From the test results of the embodiment and comparative example 3, it can be seen that the added flat chopped glass fibers have a boron content of 6 wt % and a dielectric constant of 5.4, which leads to a significant decrease in the wave transmittance of the PC / ABS alloy material.

[0124] 5) From the test results of the embodiment and comparative example 4, it can be seen that the added glass fiber is rod-shaped chopped glass fiber with a dielectric constant of 5.4. The PC / ABS alloy material has a small melt index, low fluidity, and the largest warpage, which is not conducive to processing thin products.

[0125] 6) From the test results of the embodiment and comparative example 5, it can be seen that: the added glass fiber is a rod-shaped short-cut high-boron glass fiber, and there is no significant difference in transmittance between the flat short-cut high-boron glass fiber, indicating that the key effect of glass fiber on the transmittance of PC / ABS alloy material lies in its dielectric constant, but the melt index of comparative example 5 decreases, the strength decreases, and the warpage increases.

[0126] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. A PC / ABS alloy material, characterized in that: The invention comprises the following components in parts by weight: 30 to 80 parts of polycarbonate resin, 10 to 40 parts of ABS resin, 10 to 30 parts of flat short-cut high-boron glass fibers, 2 to 5 parts of compatibilizer, 0.1 to 1.0 part of antioxidant and 0.1 to 1.0 part of lubricant.

2. The PC / ABS alloy material according to claim 1, characterized in that: The PC / ABS alloy material comprises the following components in parts by weight: 50-70 parts of polycarbonate resin, 10-30 parts of ABS resin, 15-30 parts of flat short-cut high-boron glass fibers, 3-5 parts of compatibilizer, 0.3-0.8 parts of antioxidant, and 0.3-0.8 parts of lubricant.

3. The PC / ABS alloy material according to claim 1 or 2, characterized in that: The polycarbonate resin has a viscosity average molecular weight of 20,000 to 30,000; and / or the polycarbonate resin has a melt index of 15 to 25 g / 10 min at 300° C. and 1.2 kg.

4. The PC / ABS alloy material according to claim 1 or 2, characterized in that: The ABS resin contains acrylonitrile monomer, butadiene monomer and styrene monomer; the content of the acrylonitrile monomer is 25wt% to 30wt%, the content of the butadiene monomer is 20wt% to 26wt%, and the content of the styrene monomer is 46wt% to 54wt%; and / or the melt index of the ABS resin at 220°C and 10kg is 38 to 44g / 10min.

5. The PC / ABS alloy material according to claim 1 or 2, characterized in that: The flat short-cut high-boron glass fiber meets at least one of the following conditions: (I) containing 18 wt% to 24 wt% of boron; (II) Length 25-30 mm; (III) cross-sectional width is 7 to 10 μm; (IV) The cross-sectional flatness ratio is 1:3 to 1:6; (V) The dielectric constant is 3 to 4.

6. The PC / ABS alloy material according to claim 1 or 2, characterized in that: The compatibilizer includes maleic anhydride grafted polypropylene, maleic anhydride grafted polyethylene, and maleic anhydride grafted polyolefin elastomer.

7. The PC / ABS alloy material according to claim 1 or 2, characterized in that: The antioxidant includes at least one of a hindered phenol antioxidant, a hydroxylamine antioxidant, and a phosphite antioxidant.

8. The PC / ABS alloy material according to claim 1 or 2, characterized in that: The lubricant includes at least one of polyethylene wax, magnesium stearate, calcium stearate, and ethylene bisstearamide.

9. A method for preparing the PC / ABS alloy material according to any one of claims 1 to 8, comprising the following steps: The components are mixed, melted, extruded and granulated to obtain the PC / ABS alloy material.

10. A millimeter wave radar device, the housing of which is made of the PC / ABS alloy material according to any one of claims 1 to 8.